Busca ativa e tratamento das infeccões do trato genital em gestantes com rastreamento positivo para diabete gestacional: repercusões maternas e perinatais - Tristão, Andréa da Rocha [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
To evaluate the prevalence of lower GTI in positive GDM screening and if early screen and treat strategy for lower GTI improved maternal and erinatal outcomes. Patients and methods: Case control study with 400 pregnant women divided into four groups according to GDM screening and screen and treat strategy for lower GTI which included a vaginal sample ollection, followed by prescription and follow-up. Results: The prevalence of ower GTI among 200 GDM screened was 68.5%. The screen and treat strategy or lower GTI in GDM screened patients improved gestational, perinatal and puerperal outcomes. The screen and treat strategy for lower GTI increased the isk for gestational age;
Keywords: Ginecologia; Obstetricia; Gravidez - Complicações